The long-term prognosis of patients with heart failure and the gene polymorphism Gln27Glu of β2-adrenoreceptors - Pyvovar, Sergiy; Rudyk, Yuriy; Kravchenko, Irina; Lozyk, Tatyana (ScienceRise: Medical Science, 2018)
The aim: to determine the influence of Gln27Glu polymorphism of the β2-adrenergic receptor gene on the long-term prognosis of patients with heart failure. Material and methods. The study included 200 patients with heart failure. The clinical course of the disease was evaluated and a genetic study of Gln27Glu polymorphism of the β2-adrenergic receptor gene was done. The material for molecular-genetic research was peripheral blood leukocytes of patients. Isolation of genomic DNA from blood leukocytes for molecular genetic studies was carried out using a commercial "DNA-sorb-B" kit in accordance with the instruction for the kit. Primer sequences were used for the polymerase chain reaction. Results. An analysis of the distribution of genotypes of the polymorphic Gln27Glu locus of the β2-adrenoreceptor gene in patients with heart failure showed that the genotype Gln27Gln occurs in 33 % of cases; Glu27Glu – in 13 %; Gln27Glu – in 54 %. Carriers of the mutant allele (G) of the β2-adrenoreceptor gene have a high incidence of atrial fibrillation (35.6 % vs. 7.7 %) over 3 years of follow-up. Hospitalization (42.0 % versus 19.2 %) and the frequency of reaching the combined end point (hospitalization + death) (54.0 % vs. 30.8 %) are greater among patients who carry the mutated G allele compared to homozygous patients with the "wild" allele C, for 3 years of observation. Polymorphism of the Gln27Glu gene of the β2-adrenoreceptor does not significantly affect the three-year mortality of patients with heart failure. Conclusions. The carriers of the mutant allele (G) of β2-adrenergic receptors have a high incidence of atrial fibrillation, hospitalization and the achievement of a combined end point (hospitalization + death) for 3 years of observation, compared to homozygous patients with the "wild-type" allele C. The polymorphism of the gene Gln27Glu of the β2-adrenoceptors does not affect the three-year mortality of patients with heart failure